The Role Of Renewable Energy In Poverty Reduction And Environmental Improvement - Subramaniam, Yogeeswari (2018)
Commonly, a good environmental quality will lead to an economic growth where at the very least environment will supply natural resources to produce goods and services. Therefore, a good environment will be essential for the sustainable economic growth. Nonetheless, for most of developing countries in the world, poverty has been the main feature where poor people may overexploit the environment resources to fulfill their needs. Hence, the present study investigates the effect of poverty on environmental deterioration using panel data of 52 developing countries.